Seasonal patterns of Myxobolus (Myxozoa : Myxosporea) infections in Barbus callipterus Boulenger, 1907 (Cyprinidae) at Adamawa - Cameroon - Georges, Fonkwa; Thomas, Efole Ewoukem; Timoléon, Tchuinkam; Abraham, Fomena; Joseph, Tchoumboue (Journal of Research in Biology, 2018)
For a detail understanding of the seasonal patterns of Myxobolus infections so as to elaborate control strategies, 305 Barbus callipterus specimens were sampled from May 2016 to May 2017 at Mapé River (Adamawa-Cameroon). After classical examination, the prevalence of infection was determined. Ten Myxobolus species were identified. Irrespective of the parasite species, fishes were more infected in the dry season (74.93%) than the rainy season (69.72%) without significant difference. Seasons did not significantly influence on the prevalence of parasites in the sizes and sex of various fishes’ class. However, Myxobolus ngassami was predominantly prevalent in male fishes during the dry season in contrast to the females. Regardless of the organ type and parasite species, the dry season was remarkably more favorable to the infection of organs. Mono and polyinfections occurred during the two seasons and whatever the season, the prevalence of polyinfection’s categories dropped with the increasing number of associated parasite species.